2015
DOI: 10.1038/srep15183
|View full text |Cite
|
Sign up to set email alerts
|

Action of multiple intra-QTL genes concerted around a co-localized transcription factor underpins a large effect QTL

Abstract: Sub-QTLs and multiple intra-QTL genes are hypothesized to underpin large-effect QTLs. Known QTLs over gene families, biosynthetic pathways or certain traits represent functional gene-clusters of genes of the same gene ontology (GO). Gene-clusters containing genes of different GO have not been elaborated, except in silico as coexpressed genes within QTLs. Here we demonstrate the requirement of multiple intra-QTL genes for the full impact of QTL qDTY12.1 on rice yield under drought. Multiple evidences are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 75 publications
3
67
0
Order By: Relevance
“…Alternatively, identification of large-effect QTLs which are more stable across environments and genetic backgrounds seems to be the most promising way of ensuring impact from genomics-assisted breeding methods. Dixit et al (2015) confirmed the multi-genic and multi-environment effectiveness of qDTY 12.1 , a large-effect QTL identified on chromosome 12 of the rice genome. They confirmed the central role of the no apical meristem (OsNAM 12.1 ) transcription factor in the activity of qDTY 12.1 together with promoters of six intra-QTL genes with NAM binding sites as well as three co-localized and/or partially co-expressed genes of OsNAM 12.1 .…”
Section: Manipulating Root System Architecture For Abiotic Stress Tolsupporting
confidence: 57%
“…Alternatively, identification of large-effect QTLs which are more stable across environments and genetic backgrounds seems to be the most promising way of ensuring impact from genomics-assisted breeding methods. Dixit et al (2015) confirmed the multi-genic and multi-environment effectiveness of qDTY 12.1 , a large-effect QTL identified on chromosome 12 of the rice genome. They confirmed the central role of the no apical meristem (OsNAM 12.1 ) transcription factor in the activity of qDTY 12.1 together with promoters of six intra-QTL genes with NAM binding sites as well as three co-localized and/or partially co-expressed genes of OsNAM 12.1 .…”
Section: Manipulating Root System Architecture For Abiotic Stress Tolsupporting
confidence: 57%
“…Initially, quantitative trait loci (QTLs) in model organisms were generally assumed to harbor one causal and multiple passenger alleles that affect a single causal gene; however, dissection of QTLs in inbred organisms has identified evidence of more than one gene in the same region. [6][7][8] In addition to identifying multiple genes at QTLs, fine-mapping efforts in model organisms have suggested multiple causal variants at a single locus. 8,9 Thus, genetic studies in model organisms suggest complex mechanisms that can involve multiple genes and variants at a single locus.…”
Section: Introductionmentioning
confidence: 99%
“…S9). A multiple intraQTL in the qDTY 12.1 region centered on the NAM gene (OsNAM 12.1 ) was suggested to provide a concerted drought response (Dixit et al 2015). In our study, all genes in the qDTY 12.1 region but one (LOC_Os12g29220, nodulin Mt3, OsMtN3 12.1 ) co-localizing with the NAM gene were not expressed (Table S1).…”
Section: Test Of Ase In the Hybridmentioning
confidence: 61%